ПРАЦЕЗДАТНІСТЬ РІЗАЛЬНОГО ІНСТРУМЕНТУ, ОСНАЩЕНОГО КОМПОЗИТАМИ З ВИСОКИМ ВМІСТОМ cBN, ПРИ ТОЧІННІ ЗАГАРТОВАНОЇ СТАЛІ З УДАРНИМ НАВАНТАЖЕННЯМ - Клименко, Сергій; Клименко, Сергій Ан.; Мельнійчук, Юрій; Мельнійчук, Марина; Чумак, Анатолій; Манохін, Андрій; Мельнійчук, Богдан (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2025)
The article investigates the performance of a cutting tool equipped with polycrystalline composites based on cubic boron nitride (PcBN) with a high cBN content (up to 97%) during turning of hardened steel HVG under impact loading conditions. Experimental studies of the influence of the geometric parameters of the tool, in particular the angle of inclination of the cutting edge (λ = 0–50°), on the nature of tool wear, the stability of the cutting process and the quality of the machined surface were conducted. It was established that the use of tools with λ = 40° provides the highest stability (up to 50–60 min) and allows for effective machining at increased feeds (S = 0,40–0,65 mm/rev). The results obtained confirm the feasibility of using a PcBN tool with an oblique design for high-performance turning of hardened iron-carbon alloys under dynamic loading conditions.